The Foundations in Construction, a General and Comprehensive Study from an Engineering and Historical Perspective - Arfat Hussein Mohammed Baker; Muhammed Ikhsan Setiawan; Adi Prawito (NAROTAMA UNIVERSITY, Indonesia, 2022)
The bottom base of the structure is the very uppermost part because it connects the superstructure of the body to the ground. This bottom base is known as the foundation. In this paper we will discuss and analyze the types of foundations used in the construction industry, there is a design and also in alternative materials that we can use as foundation materials in construction that can make it more solid, durable and environmentally friendly. It is critical to build a stable base that maintains the superstructure in all climatic conditions without collapsing or deteriorating the concrete structure. If any unsuitable material is used for the foundation of the structure, the high risk is the collapse of the structure. Different types of foundation base are used in different types of structural structures, each with a unique design and specific configuration that makes a particular structure more durable and stable. A different type of foundation is used in cottages and high-rise buildings. This study presents the use of foundations for the superstructure, and appropriate design, and we will discuss more precisely about how to make the foundation foundation environmentally friendly, cost-effective for the structural building, and make it more durable and strong to withstand natural and environmental disasters.